TGT For Student Collaboration In Elementary School Pancasila Education: An Effective Solution Or Just An Alternative? - Neo Fanda Bintang Purnalyta; Nita Dwi Ariyanti; Maya Candra Dewi; Deni Zein Tarsidi (CAKRAWALA: Journal of Citizenship Teaching and Learning, 2024)
One of the main functions of education is to develop collaboration and cooperation skills among students, especially in Pancasila Education learning. However, the low collaboration skills of students in the classroom often hinder the effectiveness of the learning process. Therefore, a learning approach is needed that can create a fun, engaging, and interactive learning atmosphere to enhance students' collaboration skills. This study aims to analyze the use of the Team Games Tournament (TGT) type of cooperative learning model as a solution to improve students' collaboration skills. The TGT model is implemented through the stages of class presentation, team formation, games, matches, and group awards. This study uses a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation to gain an in-depth understanding of the implementation of TGT in learning. The research results show that the implementation of the TGT learning model has a positive impact on the improvement of students' collaboration skills. This model is capable of creating an interactive learning environment, enhancing the active involvement of students, and strengthening teamwork, especially in Pancasila education. Additionally, this model also encourages healthy competition among groups, which can enhance the overall learning motivation of students. Thus, TGT can become one of the effective learning models to support the achievement of educational goals that not only focus on understanding the material but also on developing collaboration skills as preparation for social life.